How much groundwater can we pump and protect environmental flows through time? Presumptive standards for conjunctive management of aquifers and rivers. (25th August 2017) - Gleeson, T.; Richter, B.
Abstract: Groundwater is a critically important source of water for river, wetland, lake, and terrestrial ecosystems, yet most frameworks for assessing environmental flows have ignored or not explicitly included the potential impacts of groundwater pumping on environmental flows. After assessing the processes and existing policies for protecting streamflow depletion from groundwater pumping, we argue that a new groundwater presumptive standard is critical as a placeholder to protect environmental flows in rivers lacking detailed assessments. We thus extend the previous presumptive standard to groundwater pumping, a different and important driver of changes to streamflow. We suggest that "high levels of ecological protection will be provided if groundwater pumping decreases monthly natural baseflow by less than 10% through time." The presumptive standard is intended to be a critical placeholder only where detailed scientific assessments of environmental flow needs cannot be undertaken in the near term. We also suggest a new metric, the environmental flow response time, that allows water managers to quantify the timescales of the impacts of groundwater pumping on the loss or gain of environmental flows.